Advances in Ginsenosides - Chen, Jen-Tsung (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book collected recent innovative research and review articles on analytical techniques, production protocols, biotechnological tools, and new insights into bioactivities of ginsenosides including the effects on epithelial-mesenchymal transition, hippocampal neurogenesis and inflammation as well as on diseases such as ischemic stroke, autoimmune diseases, and allergic disorders. Additionally, the analysis through molecular docking and an overview of the Panax ginseng pharmacopuncture were also presented.